"This is not Something that I Share with Everyone”: Digital Media Use and One Night Stand in Indonesia - Irmawan Rahyadi; Dian Susilowati (Global Education Journal, 2026)
This article offers an understanding of digital media, intimate relationships, urban lifestyles, and moral norms for contextualizing the study of the construction of contemporary urban identity. It provides an overview of key issues in the mediated interactions of urban youth and online interactions, especially the tensions around choice and social stigma, which can limit the social values in the urban community. It also offers a reflection of the tension between individual pleasure and moral standards in the region. These data are based on a study from the cities in Indonesia, comprehensively interviewing how 20 youths in the region experience ONS to some extent. The findings are guided by the thematic analysis of the data and provide insights into categories of significance of mediated connections, intimate practices, and areas of social values, including youth, urban, ethics, culture, and modesty.